Development of the Method of Identification and Quantitation of Active Ingredients in Suppositories â€œPhytoprostâ€ - Ivko, T. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Development of the method of identification and quantitation of the active ingredients in â€œPhytoprostâ€ suppositories for the treatment of prostatic hyperplasia. Materials and Methods: Identification and quantitation of sterols in suppositories â€œPhytoprostâ€ with preliminary received unsaponifiable substances were carried out by gas chromatography using a gas chromatograph Shimadzu GC 14-B in the following configuration: Flame-ionization detector, of capillary quartz column measuring 25 m Ã— 0.25 mm with applied stationary phase of poly[methyl (94)phenyl(5)vinyl(1)]siloxane (SE-54) with a layer of 0.25 microns. Results and discussion: Development of the method of identification and quantitation was conducted in accordance with the requirements of the general article 2.4.23 of the State Pharmacopoeia of Ukraine 2.0, p. 194 on the base of the laboratory of pharmacological analysis of the State Company â€œUkrainian scientific pharmacopoeia center of the quality of medicines.â€ Test for sterols consists of two parts: Receipt of unsaponifiable substances in accordance with the requirements of general article 2.5.7 of the State Pharmacopoeia of Ukraine 2.0, p. 214, and determination of the composition of sterols in the unsaponifiable remainder by gas chromatography method in accordance with the requirements of the general article 2.4.23 of the State Pharmacopoeia of Ukraine 2.0, p. 194. Identification of sterols was carried out in the presence of campesterol, stigmasterol, Î”7-campesterol, Î”5,23-stigmasterol, and Î²-sitosterol. The chromatogram of the test solution should exhibit peaks with such relative retention times: 0.84 (campsterine), 0.88 (stigmasterol), 0.93 (Î”7-campsterine), 0.95 (Î”5.23-stigmasterol), and 1.0 (Î²-sitosterol). Conclusion: The method of identification and quantitation of active substances (plant extracts - the fruits of Palma Sabal, the root of Nettle, and Pumpkin seeds) was developed in the suppositories â€œPhytoprostâ€ for the treatment of prostate hyperplasia. Identification and quantitation of active substances were carried out according to the content of the sterol fraction by gas chromatography with a preliminary preparation of unsaponifiable substances. It is established the composition of the sterol fraction of the unsaponifiable substances and quantitation of sterols in a single suppository in terms of Î²-sitosterol.